Fenomena Money Politik dalam Pilkades Tahun 2022: Studi Kasus Desa Soki, Kecamatan Belo, Kabaputen Bima - Maemunah Maemunah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The Village Head Election is an event used to select and elect the leader of a village in every six years. However, in its implementation the village head election is constantly colored by several frauds, one of them is the phenomenon of money politics. This research was conducted with the aim of revealing and knowing the phenomenon of money politics that occurred in the election process. This research was conducted with a qualitative description in order to obtain in-depth information. Data collection methods in this study are observation, interviews and documentation. The results showed that in the election of the village head of Soki, Belo sub-district, Bima district, the practice of political money is still running, where the form was not only the distribution of money but also goods and others.